Optimization of a Fast Condiment Production Process Using the Distillers’ Grains of Shaoxing Rice Wine - Deyong Zhang, Xiaolu Xu, Yin Lu, Caiqin Liu (Forest Chemicals Review)
The main components of the distillers’ grains of Shaoxing rice wine were determined. A fast production process of a condiment, rice wine sauce, was then established using the distillers’ grains. The process mainly depends on the flavourzyme’s hydrolysis, supplemented with acidolysis pretreatment. Orthogonal experiments were conducted to optimize such steps as the pre-fermentation, acidolysis pretreatment, enzymolysis, decolorization/debittering, rice wine sauce formula. Enzymolysis, the most important step, was optimized as ‘flavorzyme 4%+ enzymolysis temperature 55℃+ enzymolysis time 6h’. The influence capability of the 3 factors is enzyme dosage, reaction time and reaction temperature in descending order. Sensory evaluation showed that the condiment got similar scores with that made using traditional method.